CAD/CAM in Orthodontics – A Magnanimous Journey - Manisha, V; Rajesh, Nallakunta (International Journal of Dental Materials, 2023)
Orthodontics is one branch of dentistry which deals with dynamic manipulation and function of the stomatognathic system. Likewise, it has to witness the dynamic changes in its diagnosis method and treatment planning. The field of orthodontics has witnessed many revolutionary techniques and evolved enormously in terms of benefiting the patient. CAD/CAM is one promising methodology that has shown a significant impact in modern dentistry and surpassed some of the challenges an orthodontist has been facing all these years. It has changed the view through which we see the patient’s condition. The application of 3D technology allows the practitioner and patient to utilize virtual treatment planning software to better identify case objectives and visualize treatment outcomes. CAD/CAM has many applications in orthodontics, which include aids for diagnosis and treatment planning, clear aligner treatment, customized lingual appliances, customized brackets with patient-specific torque, machine-milled indirect bonding jigs, robotically bent archwires, indirect bonding systems, customization of orthodontic appliances like distalization appliance etc., Acceleration of orthodontic treatment (OT) has received growing attention in recent years, especially in adult patients. Digital workflow is the current trend in orthodontic practice and has speckled every aspect of orthodontics in terms of documentation, study casts, analysis of dental malocclusion, smile designing, treatment planning and fabrication of orthodontic appliances. The current article aimed to establish a narrative description of the digital workflow and applications of the CAD/CAM process in Orthodontics.